Mildred Hall School, Yellowknife, NWT ... - Campbell, Sandy (University of Alberta Library, 2015)
Mildred Hall School is on Franklin Ave, close to downtown Yellowknife. The school has basketball courts, which were in use until very late at night, because the midnight sun provides enough light to play. ...